Changing paradigms in the treatment of systemic lupus erythematosus - Antonis Fanouriakis; George Bertsias (Lupus Science and Medicine)
SLE poses formidable therapeutic challenges due to its heterogeneity and treatment decisions often cannot be guided by data of high quality. In this review, we attempt to provide insights regarding the treatment of SLE in everyday clinical practice, based on contemporary evidence and our own personal experience. We focus on common therapeutic issues and dilemmas arising in routine care, including monitoring for retinal toxicity associated with hydroxychloroquine, handling of glucocorticoid regimens in order to minimise their adverse events, choice of immunosuppressive medications based on prevailing disease manifestations and optimal use of available biological agents (belimumab and rituximab). We also provide our view on the position of calcineurin inhibitors in the management of lupus nephritis and conclude with remarks on the future perspectives for this challenging disease.